2004
DOI: 10.1007/s00428-004-1062-9
|View full text |Cite
|
Sign up to set email alerts
|

Localised pleural malignant mesothelioma. Report of two cases simulating pulmonary carcinoma and review of the literature

Abstract: Localised malignant mesotheliomas are unusual and predominantly intrapulmonary growth is rare. Pathologists should be aware of this possibility to avoid misdiagnosis, particularly in small biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…9,12,18 These findings are comparable to those of the present investigation in that those tumors with a high number of mitoses (45 per 10 HPF), a decrease in cell cohesion, highly atypical nuclei that vary in their size and often contain cytoplasmic inclusions, and large, sometimes multiple nucleoli tend to behave in a more aggressive manner than those in which the mitotic activity was low, the cells were more uniform and more cohesive, and the nuclei exhibited less atypia. In the present series, 7 of the cases (Cases 1, 2, 6, 7, 8, 13, and 15) that were considered to belong to the first group died of disease 4-17 months (mean, 7 months) after diagnosis, while 9 of the 10 cases ( Cases 5,12,14,16,17,18,19,20, and 21) that were considered to belong to the second group died of disease 6-62 months (mean, 22 months) after diagnosis and the remaining patient (Case 4) was alive 25 months following diagnosis (Table 3). These observations appear to be in agreement with a recent investigation that indicated that nuclear grading based on nuclear features and mitotic count can provide prognostic information in epithelioid diffuse malignant pleural mesothelioma.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…9,12,18 These findings are comparable to those of the present investigation in that those tumors with a high number of mitoses (45 per 10 HPF), a decrease in cell cohesion, highly atypical nuclei that vary in their size and often contain cytoplasmic inclusions, and large, sometimes multiple nucleoli tend to behave in a more aggressive manner than those in which the mitotic activity was low, the cells were more uniform and more cohesive, and the nuclei exhibited less atypia. In the present series, 7 of the cases (Cases 1, 2, 6, 7, 8, 13, and 15) that were considered to belong to the first group died of disease 4-17 months (mean, 7 months) after diagnosis, while 9 of the 10 cases ( Cases 5,12,14,16,17,18,19,20, and 21) that were considered to belong to the second group died of disease 6-62 months (mean, 22 months) after diagnosis and the remaining patient (Case 4) was alive 25 months following diagnosis (Table 3). These observations appear to be in agreement with a recent investigation that indicated that nuclear grading based on nuclear features and mitotic count can provide prognostic information in epithelioid diffuse malignant pleural mesothelioma.…”
Section: Discussionmentioning
confidence: 65%
“…5 In these reports, however, it was demonstrated that mesotheliomas with deciduoid features can also originate in the pleura, occur in elderly men, and be associated with asbestos exposure. Since then, several other cases, mostly individual case reports, have been published [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] (Table 1). Although patient survival in many of the published cases has been short and limited to a few months after diagnosis, thus suggesting that deciduoid mesotheliomas have an aggressive clinical course, patients with long survival …”
mentioning
confidence: 99%
“…1,2 Typical clinical presentations include bloody body cavity effusion and macroscopic findings of tumor nodules or diffuse thickening of the serosal surface ( Figure 1). Rarely, MM presents with a localized mass 3 (see below). Unilateral, recurrent, hemorrhagic pleural effusion is the predominant clinical finding in most patients with diffuse pleural MM.…”
Section: Epithelioid Malignant Mesotheliomamentioning
confidence: 99%
“…Most reported cases of localized MM have developed in the pleura or as intrapulmonary or mediastinal tumors, but peritoneal localization and even hepatic and pancreatic tumors with visceral peritoneal origin have also been reported. 3,[74][75][76][77] All histologic subtypes and different morphologic patterns of MM have been described in association with localized MM. Localized MM has a better prognosis than diffuse MM because it is often surgically treatable.…”
Section: Localized MMmentioning
confidence: 99%
“…Until now, 44 MDM cases have been documented in the literature (Table I). 1–24 The deciduoid features of malignant mesothelioma was first characterized by Talerman et al in a 13‐year‐old girl where the authors reported primary peritoneal malignant mesothelioma consisting of conspicuous large cell clusters containing deciduoid‐like cells 1. Later in 1994, Nascimento et al described a mass with similar morphological features in a peritoneal lesion of a young woman and named it as MDM as a new entity 2…”
Section: Cases Of Deciduoid Mesotheliomamentioning
confidence: 99%